Highly Sensitive, Fast Response and Selective Glucose Detection Based on CuO/Nitrogen‐doped Carbon Non‐enzymatic Sensor. Issue 11 (26th April 2022) - Figiela, Monika; Wysokowski, Marcin; Stanisz, Ewa; Hao, Derek; Ni, Bing‐Jie
Abstract: This work presents development of an innovative CuO/nitrogen‐doped carbon composite (CuO−C) that may be effectively applied for the modification of a glassy carbon electrode (GCE) and creation of a non‐enzymatic sensor for glucose detection. The structure of the CuO−C nanostructured material was analyzed by scanning electron microscopy, Fourier transform infrared spectroscopy, X‐ray diffraction, and atomic absorption spectroscopy. The prepared electroactive material, based on CuO including carbon structures derived from chitosan, showed excellent performance in terms of electrocatalytic oxidation of glucose. Under optimal conditions, the modified electrode displays high sensitivity (1546 μA mM −1 cm −2 ), a low detection limit (1.95 μM) and short response time (4 s). Abstract :